Tradisi Khotmul Qur’an Rutinan Minggu Pagi: Kajian di Musholla Muhammad Jamhari Desa Gembongan Kecamatan Gedeg Kabupaten Mojokerto - Muhammad Mishbahul Munir; Mishbahush Shudur; Ahmad Fathurrobbani (Sumbula: Jurnal Studi Keagamaan, Sosial dan Budaya, 2025)
This study aims to examine one of the Living Qur'an, namely the tradition of khotmul Qur'an. The object of this study is located in Gembongan Village, Gedeg District, Mojokerto Regency. Khotmul Qur'an is held with the hope that the Qur'an will be more alive and attached to the community, especially the residents of Gembongan Village. This research is a type of field research. The data collection technique is through observation, interviews and documentation. While the data analysis technique uses the Mils and Huberman model, namely analysis consisting of three activity flows that occur simultaneously, namely: data reduction, data presentation, drawing conclusions/verification. The results of this study explain that the motives of the congregation in participating in this khotmul Qur'an activity vary, such as enlivening the prayer room so that the prayer room is more functional for religious activities, being told by their religious teachers with the aim of facilitating reading the Qur'an and to avoid bad associations. Keywords: Living Qur'an, Khotmul Qur'an, Congregation